Performance of Chaos-Based Encryption Algorithm for Digital Image - Suryadi MT; Eva Nurpeti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Presentation of information in digital form is highly vulnerable againts information abusing. Digital image is one of digital information which is frequently becomes a target of crime. Therefore, reliable, secure, and fast security technique are required in digital image information. In this study, chaos-based encryption algorithm for digital image is built to improve endurance from brute force and known plaintext attack. The algorithm using logistic map as a random number generator for key stream. According to test and analysis, this algorithm has key space of , key sensitivity up to , the key stream is proved random, and the distribution of pixels value from encrypted image is proved uniform. So, it can be concluded that, the algorithm is very difficult to be cracked by brute force attack and also known plaintext attack.